Demographic and clinical characteristics of patients with benign bone tumors: Evidence of bimodal age distribution in a Hispanic population - Blake C. Martin; Mohammad Khalil; Juan Lopez-Alvarenga; Michael Sander (Journal of Orthopaedic Reports)
Background: As far as researchers know, there's no way to prevent BBTs from forming. Although these tumors generally do not metastasize, they can still be dangerous as they may grow and compress healthy tissues and lead to poor outcomes. The principal objective was to evaluate the demographic and clinical characteristics linked to BBTs in individuals from the Rio Grande Valley. We hypothesized that older age and males would have greater frequency of BBTs. Methods: This was a retrospective chart review and IRB approval was obtained prior to starting this study. We obtained medical charts for individuals who had been diagnosed with benign bone tumors by using the ICD-10 code D16 which indicates benign neoplasm of bone and articular cartilage. Patient demographics that were included were age, sex, date at diagnosis, DOB, BMI, race, ethnicity, county of residence, and marital status. We used descriptive statistics for continuous variables, average (SD), and nominal variables, frequency, and percentage. We also used dot plots to analyze the distribution and modes. Results: A total of 89,135 charts were reviewed and a cohort of 108 patients with BBTs was examined between January 1, 2028 and September 4, 2024. This indicates an incidence rate of 0.00018 per person-year. The average age was 38.8 years (SD 24.0), with females representing 58 % of the sample. The mean BMI was 28.4 kg/m^2 (SD 7.4), and Hispanics constituted 73 % of the sample. The majority resided in Hidalgo County (71 %), and the UTHealth Orthopedic clinic was the predominant consultation venue, with 91 % of participants utilizing it. The age-by-sex distribution exhibited a bimodal pattern for under 20 and over 50 years of age. Conclusion: The RGV is a unique region with a distinct set of qualities such as decreased healthcare accessibility and quality, a large number of unemployed and uninsured individuals, numerous undocumented immigrants, and being poverty stricken. The results of this study illustrate the need for further studies and policy interventions for this population to better the understanding, prevention and management of BBTs in this population.